Can Providing Daily Iron-Fortified Lunches to School-Going Children Living in an Impoverished Region of Guatemala Improve Hemoglobin and Hematocrit Values?. (29th May 2020) - Beerman, Kathy; Ratts, Manichanh; Mitchell, Thomas; Perez, Alejandra; Solorio, Alondra; Rodríguez-Vivaldi, Ana Maria; Massey, Llesinia; McGeehan, Steven; Cotten, Chris
Abstract: Objectives: To determine if daily iron-fortified school lunches improve iron status in school-going children living in an impoverished region of Guatemala. Methods: Methodology using Lucky Iron Fish to prepare large quantities of iron-fortified food was developed. School cooks were trained how to use Lucky Iron Fish to prepare 200–300 school lunches/day. Baseline hemoglobin and hematocrit measures were taken at the study onset and again upon completion of the school year. Throughout the school year (9-mo), children received a daily iron-fortified school lunch. Pre- and post-measures (hemoglobin, hematocrit, weight, and height) were taken ( n  = 370; ages 5 to 17 y). Results: Overall paired t-tests, which were used to compare pre- and post measures, increased significantly ( P < 0.05). Paired t-test comparisons by quartiles, adjusted for regression to the mean, indicated that those with the lowest hemoglobin and hematocrit values at baseline had the greatest improvement ( P < 0.0001). Furthermore, subjects in the upper quartiles at baseline had minimal change or no change at all, suggesting that iron-fortification of food was not harmful to those with healthy iron status. Conclusions: Study results indicate that providing daily iron-fortified school lunch can effectively improve iron status in students living in impoverished regions. Funding Sources: Stawberry Jam, ngo Lucky Iron Fish Enterprise donated 25 LIF for this study.